The Role of Series Cholecystectomy in High Risk Acute Cholecystitis Patients Who Underwent Gallbladder Drainage - Wang, Chi-Chih; Tseng, Ming-Hseng; Wu, Sheng-Wen; Yang, Tzu-Wei; Sung, Wen-Wei; Wang, Yao-Tung; Lee, Hsiang-Lin; Shiu, Bei-Hao; Lin, Chun-Che; Tsai, Ming-Chang (Frontiers in Surgery, 2021)
Background Cholecystectomy (CCY) is the only definitive therapy for acute cholecystitis. We conducted this study to evaluate which patients may not benefit from further CCY after percutaneous transhepatic gallbladder drainage (PTGBD) has been performed in acute cholecystitis patients. Methods Acute cholecystitis patients with PTGBD treatment were selected from one million random samples from the National Health Insurance Research Database obtained between January 2004 and December 2010. Recurrent biliary events (RBEs), RBE-related medical costs, RBE-related mortality rate and an RBE-free survival curve were compared in patients who accepted CCY within 2 months and patients without CCY within 2 months after the index admission. Results 365 acute cholecystitis patients underwent PTGBD at the index admission. A total of 190 patients underwent further CCY within 2 months after the index admission. The other 175 patients did not accept further CCY within 2 months after the index admission. RBE-free survival was significantly better in the CCY within 2 months group (60% vs. 42%, p<0.001). The RBE-free survival of the CCY within 2 months group was similar to that of the no CCY within 2 months group in patients ≥ 80 years old and patients with a Charlson Comorbidity Index (CCI) score ≥ 9. Conclusions We confirmed CCY after PTGBD reduced RBEs, RBE-related medical expenses, and the RBE-related mortality rate in patients with acute cholecystitis. In patients who accepted PTGBD, the RBE and survival benefits of subsequent CCY within 2 months became insignificant in patients ≥ 80 years old or with a CCI score ≥ 9.